Role of mitochondrial translation in remodeling of energy metabolism in ER/PR(+) breast cancer - Koc, Emine C.; Koc, Fatih C.; Kartal, Funda; Tirona, Maria; Koc, Hasan (Frontiers in Oncology, 2022)
Remodeling of mitochondrial energy metabolism is essential for the survival of tumor cells in limited nutrient availability and hypoxic conditions. Defects in oxidative phosphorylation (OXPHOS) and mitochondrial biogenesis also cause a switch in energy metabolism from oxidative to aerobic glycolysis contributing to the tumor heterogeneity in cancer. Specifically, the aberrant expressions of mitochondrial translation components such as ribosomal proteins (MRPs) and translation factors have been increasingly associated with many different cancers including breast cancer. The mitochondrial translation is responsible for the synthesis 13 of mitochondrial-encoded OXPHOS subunits of complexes. In this study, we investigated the contribution of mitochondrial translation in the remodeling of oxidative energy metabolism through altered expression of OXPHOS subunits in 26 ER/PR(+) breast tumors. We observed a significant correlation between the changes in the expression of mitochondrial translation-related proteins and OXPHOS subunits in majority of the ER/PR(+) breast tumors and breast cancer cell lines. The reduced expression of OXPHOS and mitochondrial translation components also correlated well with the changes in epithelial-mesenchymal transition (EMT) markers, E-cadherin (CHD1), and vimentin (VIM) in the ER/PR(+) tumor biopsies. Data mining analysis of the Clinical Proteomic Tumor Analysis Consortium (CPTAC) breast cancer proteome further supported the correlation between the reduced OXPHOS subunit expression and increased EMT and metastatic marker expression in the majority of the ER/PR(+) tumors. Therefore, understanding the role of MRPs in the remodeling of energy metabolism will be essential in the characterization of heterogeneity at the molecular level and serve as diagnostic and prognostic markers in breast cancer.